Children’s Epistemic Disclaims of Knowledge in Colloquial Jakartan Indonesian - Mutiara, Rika; Agustina, Noni; Baharudin, Erwan (Masyarakat Linguistik Indonesia, 2025)
The present study explores the interactions of adults and children where the adults question children’s disclaim of knowledge in Colloquial Jakartan Indonesian (CJI). It reveals how children display their disclaims and deal with the issues of epistemic responsibility. The source of the data is Child Language Data Exchange System (CHILDES) corpus. The lexical patterns of various interactions were observed. The data was analyzed based on some theories of epistemics as stated by Heritage (2012). Lexical items to depict adults’ disbeliefs of children’s disclaims were found in the questions. Such questions appeared because the adults believed the children had epistemic access to the requested knowledge. Some children finally provided relevant knowledge after they were reminded of their epistemic statuses. Disclaims of knowledge were still found even though some questions to elicit the responses had been given. They even ended the discussion on the topic and switched to another topic. They connected their disclaims of knowledge with the state of not remembering. It shows they understood the states of not knowing and not remembering functions to indicate their inability to provide knowledge. Thus, they used the disclaims to manage the talk and show their authority.